Impact of adjuvant chemotherapy regimen on survival outcomes in immunohistochemical subtypes of ampullary carcinoma. Issue 2 (15th December 2019) - Al Abbas, Amr I.; Falvello, Virginia; Zenati, Mazen; Mani, Ashika; Hogg, Melissa E.; Zeh, Herbert J.; Singhi, Aatur; Bahary, Nathan; Zureikat, Amer H.
Abstract: Background and Objectives: Ampullary adenocarcinoma (AA) is classified by immunohistochemical (IHC) subtypes into intestinal (IN), pancreatobiliary (PB), and ambiguous (AM). The impact of adjuvant therapy on IHC subtype and disease stage is unclear. We examined the effect of adjuvant chemotherapy regimen on survival of ampullary cancers by IHC subtype and disease stage. Methods: Review of pancreatoduodenectomy (PD) performed for AA between 2005 and 2013 at a single center. The impact of regimen on IHC subtype and stage was analyzed. Results: One hundred and twenty‐one patients were subtyped: IN = 32%, PB = 48%, and AM = 20% with overall survival of 45.6, 31.3, and 46.9 months, respectively. PB had higher pathologic T‐stage, positive lymph node disease, and perineural and lymphovascular invasion ( P < .05). 5‐Fluorouracil (FU)–based adjuvant therapy improved survival compared to no treatment (87.4 vs 32.1 months; P = .046), and receipt of 5‐FU emerged as an independent predictor of improved survival (hazard ratio [HR] 0.244; P = .031) regardless of subtype. 5‐FU was superior to Gemcitabine in advanced‐stage disease (stage IIB and III vs I+IIA, HR: 0.35; P < .05). Conclusions: Adjuvant therapy with 5‐FU confers a survival benefit in patients with advanced‐stage AA regardless of subtype. The impact of various chemotherapy regimens on subtypes of ampullary cancer warrants further investigation.